15‐Lipoxygenase‐Mediated Modification of HDL3 Impairs eNOS Activation in Human Endothelial Cells. Issue 4 (26th February 2014) - Cutuli, Lucia; Pirillo, Angela; Uboldi, Patrizia; Kuehn, Hartmut; Catapano, Alberico L.
Abstract: Caveolae are cholesterol and glycosphingolipids‐enriched microdomains of plasma membranes. Caveolin‐1 represents the major structural protein of caveolae, that also contain receptors and molecules involved in signal transduction pathways. Caveolae are particularly abundant in endothelial cells, where they play important physiological and pathological roles in regulating endothelial cell functions. Several molecules with relevant functions in endothelial cells are localized in caveolae, including endothelial nitric oxide synthase (eNOS), which regulates the production of nitric oxide, and scavenger receptor class B type I (SR‐BI), which plays a key role in the induction of eNOS activity mediated by high density lipoproteins (HDL). HDL have several atheroprotective functions, including a positive effect on endothelial cells, as it is a potent agonist of eNOS through the interaction with SR‐BI. However, the oxidative modification of HDL may impair their protective role. In the present study we evaluated the effect of 15‐lipoxygenase‐mediated modification of HDL3 on the expression and/or activity of some proteins localized in endothelial caveolae and involved in the nitric oxide generation pathway. We found that after modification, HDL3 failed to activate eNOS and to induce NO production, due to both a reduced ability to interact with its own receptor SR‐BI and to a reduced expression of SR‐BI in cells exposed to modified HDL. These findings suggest that modification of HDL may reduce its endothelial‐protective role also by interfering with vasodilatory function of HDL.